Customer Relationship Management Untuk Meningkatkan Daya Saing Perusahaan - Bambang Suhardi (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2006)
For corporate that compete in industry, Customer Relationship Management (CRM) strategy must be engaged ini order to remain competitive. This strategy involves marketing, sales, service, and technology which have to work together in harmony with other aspects oforganization. As a business concept, CRM gives contribution to develop marketing strategic through creating long lasting relationship with customers. The goal of CRM is to enhance the value of customer satisfaction. If customer satisfaction goals were not achieved with the implementation ofCRM then this strategy fails.